Computational Studies of Thiourea Derivatives as Anticancer Candidates through Inhibition of Sirtuin-1 (SIRT1) - Arry Yanuar; Ruswanto Ruswanto; Richa Mardianingrum (Jurnal Kimia Sains dan Aplikasi, 2022)
Cancer is a disease that starts from the uncontrolled growth of abnormal cells in the organs or tissues of the body, which is the second leading cause of death in the world. One of the targets in discovering and developing anticancer drugs is Sirtuin-1. SIRT1 can act as a tumor suppressor or tumor promoter depending on its target in a particular signalling pathway or on particular cancer. This study aimed to study the interaction of a thiourea derivative with SIRT1 (PDB ID:4I5I) through its inhibition of histone deacetylase. Research has been carried out in silico with molecular docking (MGLTools.1.5.6) and molecular dynamics (Desmond 2019) of three thiourea derivatives to the receptor. In addition, pharmacokinetic parameters, toxicity, and selection of Lipinski's Rule of Five were also tested. Molecular docking results showed that compound b ([2-(methylcarbamothioylcarbamoyl)phenyl]benzoate) had the lowest ∆G value of −9.29 kcal/mol with a KI value of 0.156 µM compared to other thiourea derivatives and was proven by molecular dynamics tests for 30 ns and amino acids that play an active role in the interaction include the residue PheA:297. In terms of pharmacokinetics and toxicity, compound b is better than natural ligands. Compound b is predicted to be used as an anticancer candidate through further research.